Disease progression of nonalcoholic steatohepatitis in Taiwanese patients: a longitudinal study of paired liver biopsies. Issue 2 (February 2019) - Lin, Ta-Ya; Yeh, Ming-Lun; Huang, Chung-Feng; Huang, Ching-I; Dai, Chia-Yen; Hsieh, Meng-Hsuan; Chen, Shinn-Chern; Huang, Jee-Fu; Yu, Ming-Lung; Chuang, Wan-Long
Abstract : Objectives: Nonalcoholic steatohepatitis (NASH) might progress to fibrosis, cirrhosis, and hepatocellular carcinoma. However, the natural history of NASH has not been fully clarified. This study aimed to investigate the disease progression in NASH patients receiving paired liver biopsies. We also aimed to examine the factors associated with NASH progression. Patients and methods: Ten NASH patients who had received liver biopsies during June 2001 and February 2010 were consecutively enrolled. The histopathological changes were examined retrospectively, including nonalcoholic fatty liver disease activity score (NAS) and fibrosis stage. The associated clinical profiles were also analyzed. Results: The median duration between paired biopsies was 20.5 months (range: 12–106 months). According to NAS and fibrosis stage, disease progression, stable disease, and disease regression were observed in seven patients, two patients, and one patient, respectively. Six (60%) patients had increased NAS on second biopsy, and two were lean NASH patients. The only patient with an improvement in NAS had achieved body weight reduction (13.3%) between paired biopsies. None of the 10 patients experienced an improvement in fibrosis. Five (50%) patients showed progression of fibrosis on second biopsy and the annual fibrosis progression rate was 0.32/year. Two of the five patients who showed progression of fibrosis were of the nonobese phenotype, whereas three patients were nondiabetic. Conclusion: NASH is a progressive disease in Taiwanese patients. The disease progression should be further clarified in lean and nondiabetic NASH patients.